Moms with ADD : A Self-Help Manual - Adamec, Christine A.; Foreword by Gwinnell, Esther (Lanham, Maryland Taylor Trade Publishing, 2000)
Guaranteed to make moms with ADD happier at home and at the office.
Include Appendices, Bibliography and Index.
A Self-Help Manual
Keywords: Mothers--Mental health -- Attention-deficit disorder in adultss -- ttention-deficit-disordered adults--Family relationships